Accelerating the crosslinking process of hyperbranched polycarbosilane by UV irradiation. Issue 10 (August 2017) - Zhong, Xiqiang; Pei, Xueliang; Miao, Yulong; He, Liu; Huang, Qing
Abstract: A liquid hyperbranched polycarbosilane (LHBPCS) with stoichiometric C/Si ratio but without unsaturated groups was synthesized. Different from traditional thermal crosslinking, ultraviolet (UV) irradiation crosslinking was taken. The molecular weight, the consumption of SiH group and ceramic yield of LHBPCS showed an increase trend with increasing the UV irradiation time. After 30 min of UV irradiation, 71.8 wt% ceramic yield was obtained. In addition, extra divinyldimethylsilane was added into LHBPCS. Under UV irradiation, both the SiH group and vinyl group of divinyldimethylsilane were consumed. But the reaction extend of vinyl group was much faster than that of SiH group. Compared with pure LHBPCS, the mixture of LHBPCS and 5 wt% divinyldimethylsilane gave a higher ceramic yield of 79 wt% after 30 min of UV irradiation. By heating the crosslinked LHBPCS to 1000 °C, a near stoichiometric SiC ceramic was got. It exhibited excellent thermal stability at 1400 °C in air.